2022
DOI: 10.1136/bmjgast-2021-000794
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and liver cancer: lost patients and larger tumours

Abstract: BackgroundNorthern England has been experiencing a persistent rise in the number of primary liver cancers, largely driven by an increasing incidence of hepatocellular carcinoma (HCC) secondary to alcohol-related liver disease and non-alcoholic fatty liver disease. Here we review the effect of the COVID-19 pandemic on primary liver cancer services and patients in our region.ObjectiveTo assess the impact of the COVID-19 pandemic on patients with newly diagnosed liver cancer in our region.DesignWe prospectively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 30 publications
4
19
2
Order By: Relevance
“…We found that many of the pancreatic cancer-related services were disrupted across the pathway of care. This is in line with previous reports about healthcare being negatively affected by the COVID-19 pandemic [3][4][5][6][7][8][9][11][12][13][14]. Healthcare assessments, such as BMI, HbA1c and liver function, were delivered to fewer people than would be expected if the pandemic had not occurred.…”
Section: Summary and Findings In Contextsupporting
confidence: 89%
See 1 more Smart Citation
“…We found that many of the pancreatic cancer-related services were disrupted across the pathway of care. This is in line with previous reports about healthcare being negatively affected by the COVID-19 pandemic [3][4][5][6][7][8][9][11][12][13][14]. Healthcare assessments, such as BMI, HbA1c and liver function, were delivered to fewer people than would be expected if the pandemic had not occurred.…”
Section: Summary and Findings In Contextsupporting
confidence: 89%
“…Cancer services were already overstretched before the COVID-19 pandemic [1,2]. With the widespread effect on healthcare, the pandemic further exacerbated the cancer-related healthcare crisis [3][4][5][6][7][8][9][10][11][12][13][14]. During the pandemic, the resources, and the attention in healthcare systems globally, shifted towards preventing and managing COVID-19 [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…This has resulted in delayed presentation and hospitalisation of sicker patients with advanced cirrhosis, increased liver-related mortality and a reduction in overall patient satisfaction 59 61. The strain on healthcare resources and prioritisation of social distancing has also led to interrupted HCC surveillance programmes leading to delayed presentation and increased tumour size at diagnosis compared with the pre-pandemic era 62 63…”
Section: Covid-19 In Patients With Chronic Liver Diseasementioning
confidence: 99%
“…Consistently, HCC tumor sizes were bigger during the pandemic year (60 4.6 mm vs 48 2.6 mm, p = 0.017), and spontaneous tumor hemorrhage was more common. Slightly fewer new cases of intrahepatic cholangiocarcinoma (ICC) were reported, although symptoms were frequently present [ 87 ]. Patients with high risk of liver malignancies, particularly those with advanced tumor stages, may have high mortality rate.…”
Section: Histological Findings and Imaging Featuresmentioning
confidence: 99%